Strain performance of tilapia in freshwater prawn polyculture - Khan, MSR; Khan, MM; Akter, N; Wahab, MA (Journal of the Bangladesh Agricultural University, 2016)
Production performance of two tilapia (Oreochromis niloticus) strain viz. Chitralada and GIFT (Genetically Improved Farmed Tilapia) in fish-prawn polyculture system was compared, and possible effect of tilapia inclusion in freshwater prawn (Macrobrachium rosenbergii) culture was evaluated in 120 days of grow-out phase. There were three treatments, i.e. only freshwater prawn as control (T1), prawn + Chitralada (T2), and prawn + GIFT (T3) with three replications of each. Stocking densities for prawn juvenile was 30,000 ha-1 in all the treatments and for both tilapia strains were 10,000 ha-1. Floating feed containing 28% protein for tilapia and pelleted sinking feed for prawn were provided twice daily at a rate of 10-5% bw adjusted after each month of sampling. Water transparency was significantly lower (P<0.05) in treatment T1 with significantly higher chlorophyll-? content that increased with progression of time. Along with, plankton abundance was significantly higher (P<0.05) in T1 indicating prawn-tilapia mixed culture is better than traditional single species culture of prawn in terms of water quality management. Average individual weight, final weight, survival and production of prawn did not differ significantly (P>0.05) among the treatments. In case of tilapia, average individual weight was significantly higher in Chitralada (254.22 g) than that of GIFT (201.52 g). However, survival of GIFT was significantly higher (92.50%) than that of Chitralada (65.83%). Gross and net production of tilapia did not vary significantly. It was concluded that prawn-tilapia mixed culture is advantageous over traditional mono culture regarding production augmentation, and tilapia inclusion improving water quality. J. Bangladesh Agril. Univ. 14(1): 127-134, June 2016